Fungsi dan Makna Fengshui Bagi Kehidupan Masyarakat Tionghoa di Kota Makassar dalam Pembelajaran Pengetahuan Lintas Budaya - Erviera Hendri Rezky; Muhammad Anwar; Misnawaty Usman (Universitas Negeri Makassar, 2022)
This study aims to examine the function and meaning of feng shui for the Chinese community in Makassar City. This research is an ethnographic study. Research data were obtained through interviews. The informants of this study were selected from Chinese residents in Makassar City. The results showed that feng shui means to harmonize, balance, and harmonize between humans and the universe. Meanwhile, the function of feng shui is as a benchmark to organize and arrange buildings to create good and balanced energy to bring good luck. The learning of knowledge across feng shui cultures is a stage so that the Chinese community is aware of their own culture and the local community respects the existence of cultural diversity.Keywords: Fengshui, Chinese Society, Makassar City, Cross-Cultural Knowledge